Effect of submaximal exercise on fibrinolytic activity in ischaemic heart disease. - Khanna, P K (1975)
Fibrinolytic activity and platelet adhesiveness are normal in cases of angina pectoris and healed myocardial infarction, whereas fibrinolytic activity is diminished in acute myocardial infarction. Exercise increases fibrinolytic activity in normal people but the effect on it of submaximal exercise in patients with ischaemic heart disease is not known. Resting platelet adhesiveness and fibrinolytic activity were determined in 20 patients suffering from ischaemic heart disease and eight healthy controls. Both groups were then subjected to submaximal exercise on a motor-driven treadmill. The ST segment of the electrocardiogram and the heart rate were monitored during exercise by an on-line digital computer. Fibrinolytic activity determinations were repeated immediately after exercise. There was a significant increase in fibrinolytic response in both groups but it was significantly less in the ischaemic groups (36-2%) compared with the controls (55-9%) (P less than 0-01). The ST segment depression was 2-3 mm in the ischaemic group and 0-52 mm in controls--also a significant difference (P less than 0-01). There was no correlation, however, between the ST change and the fibrinolytic response. A diminished response in the ischaemic group may favour their predisposition to thrombotic episodes.